PERANCANGAN SISTEM INFORMASI AKADEMIK BERORIENTASI OBJEK MENGGUNAKAN UNIFIED MODELLING LANGUAGE DI UNIVERSITAS SAHID SURAKARTA - Hardika Khusnuliawati; Arif Nugraha Hernanjaya; Firdhaus Hari Saputro Al Haris (JURNAL GAUNG INFORMATIKA, 2017)
In a university, the academic process becomes one of the processes that need to be a major concern. The academic process need to run smoothly. Unfortunately, the academic process in the university of Sahid Surakarta is often hampered because the students have difficulties in taking the study plan card. Students must take the study plan card manually. Therefore, an academic information system is required that the study plan card can be accessed online by the students.The academic information system is a complex system. Object-oriented design becomes the most suitable method for this system. The system can be divided into subsystems. UML is selected as a modeling language. There will be three diagrams used to describe this system. They are use case diagram, activity diagram, and class diagram. Finally, this paper aims to design academic information system based on object-oriented approach using unified modelling language in the university of Sahid Surakarta.